Hematopoietic stem-cell gene therapy of hemophilia A incorporating a porcine factor VIII transgene and nonmyeloablative conditioning regimens - Ide, Lucienne M. (American Society of Hematology, 2007)
Insufficient expression of factor VIII (fVIII) is a major hurdle in the development of successful nucleic acid treatments for hemophilia. However, we recently showed that under myeloablative and reduced-intensity total body irradiation (TBI) conditioning, transplantation of hematopoietic stem cells (HSCs) transduced with recombinant retroviruses containing B domain–deleted porcine fVIII (BDDpfVIII) sequences provides curative fVIII levels in a hemophilia A mouse model. In the current study, we tested BDDpfVIII activity after nonmyeloablative conditioning with busulfan, cyclophosphamide, or fludarabine and immunosuppressive agents CTLA4-Ig + anti-CD40L or anti-(murine)thymocyte serum (ATS). ATS is similar in action to anti-(human)thymocyte globulin (ATG), which is used clinically with busulfan in bone marrow transplantations to increase donor cell engraftment. Mice conditioned with busulfan + ATS and that received a transplant of BDDpfVIII-transduced stem-cell antigen 1-positive cells exhibited moderate levels of donor cell chimerism (between 20% and 60%) and achieved sustained fVIII levels more than 1 U/mL. Similar results were observed in mice preimmunized with human fVIII and conditioned with 5 Gy TBI + ATS or busulfan + ATS. These data demonstrate that it is possible to achieve sufficient fVIII expression after transplantation of BDDpfVIII-transduced HSCs following low-toxicity pretransplantation conditioning with targeted immunosuppression, potentially even in the context of preexisting inhibitors.